PERBANDINGAN UNSUR-UNSUR DEUS EX MACHINA DALAM PAK BELALANG DAN RUMPELSTILTSKIN - Syam, Essy (Universitas Lancang Kuning, 2019)
This writing compares the elements of deux ex machina in two folklores entitle “Pak Belalang” and “ Rumpelstiltskin”. Thus, the objective of the research is describe and analyze the similarities and differences of the elements of deux ex machina used in eastern and western folklores because these two chosen folklores reflect the tendency of both easterners and westerners in using the elements of deux ex machina in creating the folklores. Related to that, this analysis applies descriptive analysis in which the result of the analysis will be described clearly. From the description, it will show the tendency of the eastern and western’s texts in making good use of the elements of deux ex machina which may determine the aesthethic elements of a literary work.